Microalgal consortia differentially modulate progressive adsorption of hexavalent chromium - Nath, Adi (Physiol Mol Biol Plants, 2017)
A set of experiments was conducted to provide significant insights of micro-algal consortia regarding chromium adsorption. Four monocultures; Scenedesmus dimorphus, Chlorella sp., Oscillatoria sp., and Lyngbya sp., and their synthetic consortia were evaluated initially for chromium bio-adsorption at four different regimes of hexavalent chromium i.e. 0.5, 1.0, 3.0 and 5.0 ppm. Based on findings, only 1.0 and 5.0 ppm were considered for future experiments. Consequently, three different types of monoculture and consortia cells namely; live cells, heat-killed cells, and pre-treated cells were prepared to enhance their adsorption potential. Maximal adsorption of 112% was obtained at the dose of 1.0 ppm with 0.1% SDS pre-treated consortia cells over live consortia cells. In support, atomic absorption spectroscopy, laser induced breakdown spectroscopy, pulse amplitude modulated chlorophyll fluorescence, and scanning electron microscopy were performed to assess the structural and functional changes within consortia and their utilization in mitigation of elevated chromium levels.